A Brief Overview of the Role and Function of Fixative and Fixation: Review - Dhuha Adel Kareem (University of Thi-Qar Journal of agricultural research, 2024)
Fixation is a physical chemical process that fixes tissues or cells chemically. Fixatives have many functions, one of which is to stop tissue putrefaction and autolysis. Formaldehyde, glutaraldehyde, glacial acetic acid, alcohol, mercuric chloride, potassium dichromate, osmium tetroxide, glyoxal, picric acid, Zenker,s solutions, Bouin,s solution and other fixative chemicals are used. A thorough search of the databases in Google Scholar, research gut, and Scopus revealed few papers on "fixation" and "fixative." A thorough overview of fixation and fixatives was written with this fact in mind. This review’s main objective is to acquaint pathologists and lab personnel with the core ideas and different categories of fixatives.